A psicopedagógico look at teaching multiplication of operations and division of natural numbers proposed 1st to 3 year in textbooks of early years of basic education (Research, Society and Development, 2019)
The aim of this paper is to investigate the proposed teaching of multiplication and division of natural numbers in the block related to Mathematics Literacy in a collection of textbooks approved by PNLD / 2013 early years of elementary school. Thus, it was thought to bring a psycho looking for teaching mathematics, still guided by some PIAGET learning theories (1998) and Vygotsky (1998), about both learning concepts. The choice of this theme was made from the pursuit of understanding how is the teaching of these operations in this level of education. Among the analyzes of teaching proposed by a collection of textbooks, discussions are brought referring to reflections about the teacher training this level of education. The analysis results show that the proposed teaching of multiplication and division of natural numbers in the block related to Mathematics Literacy in line with the official documents regarding the teaching suggestions in the investigated levels.